Lignans from the fruits of Schisandra chinensis (Turcz.) Baill inhibit proprotein convertase subtilisin/kexin type 9 expression. (April 2017) - Pel, Pisey; Chae, Hee-Sung; Nhoek, Piseth; Yeo, Woojin; Kim, Young-Mi; Chin, Young-Won
Abstract: Bioactivity-guided fractionation of the fruits of Schisandra chinensis, using the proprotein convertase subtilisin-kexin type 9 (PCSK9) mRNA expression screening assay, led to isolation of two previously unknown lignans, 14-tigloylschinlignan D and rel- (7 R, 8 R, 7′ R, 8′ R )-manglisin E, along with 28 known compounds. All structures were established by NMR spectroscopic data as well as CD and MS analysis. All isolates were tested for their inhibitory activities on the mRNA expression of PCSK9. Of the tested compounds, four of the compounds rel- (7 R, 8 R, 7′ R, 8′ R )-manglisin E, (−)- schisandrin C, schinlignan D, and (+)-schisandrol B potently inhibited PCSK9 mRNA expression with IC50 values of 3.15, 3.85, 0.36, and 1.10 μM, respectively. Furthermore, schinlignan D and (+)-schisandrol B were found to suppress PCSK9 protein expressions and schinlignan D deemed to increase low density lipoprotein receptor expression. Graphical abstract: Two lignans along with 28 known compounds were isolated and four lignans potently inhibited PCSK9 mRNA expression. Highlights: Fruits of Schisandra chinensis inhibited PCSK9 mRNA expression. 14-tigloylschinlignan D and rel- (7 R, 8 R, 7′ R, 8′ R )-manglisin E were identified. Four lignans potently inhibited PCSK9 mRNA expression. Schinlignan D suppressed PCSK9 protein and increased LDLR expression.